Evaluation the effect of the service quality of higher education on the doctoral students loyalty using HedPERF measurement scale at University of El-Tarf - Abidat, Sarra; Labed brinis, Cherifa (Journal of Excellence for Economics and Management Research, 2026)
The purpose of this study was to evaluate the effect of service quality of higher education on the docoral students loyalty at the University of El Tarf. The research used HEdPERF measurement scale. There were five dimensions:Non-academic aspects, Academic aspects, Reputation, Access and Program.) . The descriptive analytical was used, and questionnaire was survey using the comprehensive enumeration method. To test the hypotheses, the Statistical Package for the Social Sciences (SPSS) and appropriate statistical methods were used. The result indicated a positive influence of the service quality of higher educations in all its dimensions on the doctoral students loyalty at the University of El Tarf. Finally, the study recommends the need to support the higher education quality strategy by building strong relationships with doctoral students, focusing on providing distinguished services that contribute to providing a stimulating educational environment and meet their needs in light of current developments.